Investigating the application of artificial intelligence for earthquake prediction in Terengganu - Marhain S.; Ahmed A.N.; Murti M.A.; Kumar P.; El-Shafie A. (Springer Science and Business Media B.V., 2023)
algorithm; artificial intelligence; earthquake prediction; earthquake recurrence; regression analysis; support vector machine; uncertainty analysis; Malaysia; Terengganu; West Malaysia